Menelaah sifat-sifat kepribadian dan ketangguhan mental: analisis komparatif antara atlet tarung derajat nasional dan regional - Salsabila , Anisa; Fitri, Mustika; Williyanto , Septian; Apriady , Hilmy; Ockta , Yovhandra (Universitas Nusantara PGRI Kediri, 2025)
This research investigates whether personality type and mental toughness differ significantly between national and regional-level combat athletes, exploring if competition level impacts athletes' psychological traits. The research design was cross-sectional, involving data collection at a single point in time from two groups of athletes (national and regional) using a questionnaire distributed via Google Forms. The sample consisted of 14 advanced fighters, 7 from the national and 7 from the regional teams. Participants were recruited using purposive sampling, targeting athletes who met specific criteria for competitive experience. Data was collected through questionnaires distributed via Google Forms, and the research instruments included the EPQ-R for personality assessment and a mental toughness questionnaire. Statistical analysis used SPSS 25, which involved variance tests to ensure data validity and reliability. The study revealed no significant differences (p > 0.05) in personality type or mental toughness between the two groups. Regional athletes had a higher average EPQ-R score (34.6) than national athletes (28.85). Regarding mental toughness, only 2 national athletes scored in the